A Study of the Effect of Fines Content on the Performance of Soil as Sub-Base Material for Road Construction - Ayodele, Adekemi Loretta (2015)
This study established optimum and determined the effect of fines content on the engineering properties of lateritic soil for use as sub-base material for roads. It also developed a regression model relating the fines content to the engineering properties. This was with a view to addressing road pavement failure, a common feature of the tropical environment.